US service member tourniquet use on the battlefield: Iraq and Afghanistan 2003–2011. (July 2016) - Dunn, John C; Fares, Austin; Kusnezov, Nicholas; Chandler, Philip; Cordova, Christopher; Orr, Justin; Belmont, Philip; Pallis, Mark
Introduction: Tourniquet use has not been studied regarding specifically combat-intense military occupational specificities. This analysis examined the survivability, frequency of use, and nature of injuries in which tourniquets were employed among personnel in a single combat-specific military occupational specialty during combat operations. Methods: Injuries sustained by the combat-specific soldier, the cavalry scout, from 2003 to 2011 were identified using the Joint Theater Trauma Registry. Basic demographic information, mechanism of injury, injury characteristics, and mortality were recorded. Results: Of the 453 cavalry scouts wounded in action, 313 had adequate documentation upon arrival to a field hospital. Tourniquets were applied to 24 (7.7%) extremity wounds, 23 (96%) of these soldiers survived and one died of wounds (4.2%). Among those is in which tourniquets were used, there were seven (30%) senior enlisted and 16 (70%) junior enlisted soldiers with an average age of 24.8 years. Injuries were caused by gunshot wounds in 4 (17%), explosions in 18 (74%) and other mechanisms in two (8.3%). The primary reason for tourniquet application was open fracture ( n  = 14, 61%), followed by vascular injury ( n  = 5, 22%), and amputation ( n  = 3, 13%). Other penetrating injuries were present in 19 (83%) of scouts. Conclusion: The high survivability of patients transported with tourniquet in place underscores the importance of battlefield tourniquet application. Continued focus on education and equipping combat personnel with tourniquets is critical to survivability of the injured solider.